Respostas
respondido por:
4
P.A.(2,8...
r = a 2 - a 1
r = 8 - 2
r = 6
a 20 = a 1 = (n - 1 ) .r
a 20 = 2 + (20- 1) .6
a 20 = 2 + 19 . 6
a 20 = 2 + 114
a 20 = 116
r = a 2 - a 1
r = 8 - 2
r = 6
a 20 = a 1 = (n - 1 ) .r
a 20 = 2 + (20- 1) .6
a 20 = 2 + 19 . 6
a 20 = 2 + 114
a 20 = 116
respondido por:
4
An = A1 + (n-1).r
A20 = 2 + (20-1).6
A20 = 2 + 19.6
A20 = 2 + 114
A20 = 116
A20 = 2 + (20-1).6
A20 = 2 + 19.6
A20 = 2 + 114
A20 = 116
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás